Decay of the Charged Harmonic Oscillator - Sami M. Al-Jaber; Walter C. Henneberger (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
We apply the van Kampen-Steinwedel principal axis transformation to the problem of finding time-dependent probability distributions for decaying states of the harmonic oscillator. The result lends itself easily to computer simulation. Results for the decay of levels 1,2, and 15 are given.